(untitled) (XXI Century. Spanish Literature and Culture, 2005)
The pages of a series of notebooks between the end of 2001 and 2004 are collected with which will be composed the fifth volume of your notes, journals or notebooks. In these pages they tell anecdotes from which they derive reflections. All these anecdotes revolve around the same theme: literary criticism and the relationship that exists between it and creation. How the criticism, of any kind, not only literary but also grammatical corrections, affects the writers and how is the relationship they have with her.